Left ventricular assist device implantation improves glycaemic control: a systematic review and meta‐analysis. (27th July 2018) - Patel, Nirav; Gluck, Jason A.; Radojevic, Joseph; Coleman, Craig I.; Baker, William L.
Abstract: Aims: Heart failure (HF) and diabetes mellitus (DM) often coexist and have bidirectional association. Advanced HF is associated with worsened glycaemic control. This meta‐analysis investigated the effects of left ventricular assist device (LVAD) implantation on markers of DM control. Methods and results: We performed a systematic search of MEDLINE and Cochrane through October 2017 to identify studies evaluating advanced HF patients who had received an LVAD and reported markers of glycaemic control. The primary outcome was glycosylated haemoglobin A1c (HbA1c), and the secondary outcomes included fasting glucose, daily insulin requirements, and body mass index (BMI). Outcomes were pooled using a Hartung–Knapp random‐effects model producing a mean difference (MD) and 95% confidence interval (CI). Thirteen studies, including 820 participants, were included. HbA1c was 1.23% lower following LVAD implantation (95% CI −1.49 to −0.98). Greater HbA1c reductions were seen with higher pre‐LVAD values. Similarly, fasting plasma glucose (−24.4 mg/dL, 95% CI −33.4 to −15.5), daily insulin requirements (−18.8 units, 95% CI −28.8 to −8.7), and serum creatinine levels (MD −0.20, 95% CI −0.35 to −0.06) were significantly lower than pre‐LVAD levels. We saw no difference in BMI (MD 0.09, 95% CI −1.24 to 1.42). Conclusions: LVAD implantation was associated with significant improvement in HbA1c, fasting plasma glucose, and daily insulin need in advanced HF patients.